2007
DOI: 10.1111/j.1551-2916.2007.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Mechanism for the Continuous Reaction of γ‐Al2O3‐Modified Aluminum Powder with Water

Abstract: Previous experiments showed that γ‐Al2O3‐modified Al powder could continuously react with water and generate hydrogen at room temperature under atmospheric pressure. In this work, a possible physicochemical mechanism is proposed. It reveals that a passive oxide film on Al particle surfaces is hydrated in water. OH− ions are the main mobile species in the hydrated oxide film. When the hydrated front meets the metal Al surface, OH− ions react with Al and release H2. Because of the limited H‐soluble capacity in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
160
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 27 publications
3
160
0
Order By: Relevance
“…In another study dealing with aluminum powder, Deng et al [14][15][16] showed that water is in fact more reactive with the gamma alumina/aluminum system than with pure aluminum. It was shown that aluminum powder covered with cracked gamma alumina reacts with water to produce bohemite (AlOOH) and hydrogen gas, following the neutral reaction:…”
Section: Discussionmentioning
confidence: 96%
“…In another study dealing with aluminum powder, Deng et al [14][15][16] showed that water is in fact more reactive with the gamma alumina/aluminum system than with pure aluminum. It was shown that aluminum powder covered with cracked gamma alumina reacts with water to produce bohemite (AlOOH) and hydrogen gas, following the neutral reaction:…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4][5][6][7] Although the reaction, 2Al + 6H 2 O → 2Al(OH) 3 + 3H 2 , is exothermic, formation of an aluminum-oxide layer on the aluminum surface prevents continuous reaction. 8 In order to overcome this bottleneck, continual removal of the oxide layer has been attempted using various promoters such as hydroxides, 5 oxides, 9 and salts. 10 Unfortunately, none of these techniques has achieved a sufficiently fast rate of H 2 production for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, alumina nanoparticles are produced by a sol-gel method [9], hydrothermal method or mechanosynthesis. New methods for synthesizing nano-alumina have been developed, such as precipitation from ammonium carbonate aqueous solution and aluminum nitrate ethanol solution [10], flame spray pyrolysis [11], and high-gravity reactive precipitation [12]. Nano-sized aluminum oxyhydroxide is generated by the reaction of aluminum or aluminum nitride powders with water [13][14][15].…”
Section: Introductionmentioning
confidence: 99%